Synthesis, characterization and dielectric properties of novel phthalocyanines bearing an octa-peripherally substituted mercaptoquinoline moiety - Adam, Nurettin; Ugur, Ahmet Lutfi; Altindal, Ahmet; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The synthesis, characterization, spectral and dielectric properties of peripherally (alpha) octa-mercaptoquinoline substituted Zn(II), Lu(III), Fe(III) and In(III) phthalocyanines are described for the first time. These complexes (2-5) and their precursor are characterized by elemental analysis, FT-IR, H-1 NMR, electronic spectroscopy as well as mass spectroscopy. Complexes 2-5 have good solubility in organic solvents such as CHCl3, DCM, DM50, DMF, THF and toluene and are not aggregated in any of the solvents over a wide concentration range. The dielectric properties and the dc conduction properties of 2-5 were investigated as a function of frequency and temperature. The dielectric properties were studied in the frequency range 400-1 x 10(6) Hz. and in the temperature range 300-500 K. It has been observed that both the dielectric constant (epsilon'(omega)) and dielectric loss (epsilon ''(omega)) decrease with the rise in frequency, but increase with the rise in temperature. From the analysis of the dc conductivity (sigma(dc)) dependence on temperature, a weak temperature dependence in the low temperature region and a strong temperature dependence in the higher temperature region was observed for films of 2-5, which indicates the involvement of two conduction mechanisms. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Zinc; Lutetium; Iron; Indium phthalocyanines; Dielectric; GAS-SENSING PROPERTIES; ELECTRICAL-PROPERTIES; ZINC PHTHALOCYANINES; CONDUCTION; METALLOPHTHALOCYANINE; ZN; TEMPERATURE; COBALT; FILMS; Chemistry; Crystallography